Prevalence and associated factors of recent HIV-1 infection among newly identified HIV-positive individuals tested with the Asante Rapid Recency assay in Harari region, Eastern Ethiopia - Nure, Muzemil Ebrahim; Weldegebreal, Fitsum; Tebeje, Fikru; Sime, Akewok; Regassa, Lemma Demissie (Frontiers in Epidemiology, 2025)
BackgroundHuman immunodeficiency virus (HIV) is a virus that attacks the immune system. Globally, more than 79.3 million people have been infected with it, and about 36.3 million people have died since the beginning of the epidemic. Ethiopia is one of the major affected countries in sub-Saharan Africa, with a huge number of people living with HIV. The identification of recent HIV-1 infections plays a crucial role in guiding prevention and control interventions. Moreover, data on the prevalence and factors associated with recent HIV-1 infection among cases tested by the Asante Rapid Recency Assay at health facilities in the Harari region has been inadequate. This study aimed to assess the prevalence and associated factors of recent HIV-1 infection among newly identified HIV-positive individuals tested with the Asante Rapid Recency Assay in Health Facilities of Harari Region, Eastern Ethiopia.MethodsRetrospective cross-sectional study was employed using HIV-1 diagnoses data from April 15–20, 2024 with 580 study participants. The data were extracted based on the standardized HIV Case-Based Surveillance report form, as outlined by the Ethiopian Public Health Institute. Data extracted from Redcap were checked and cleared for completeness then entered and analysed using the Statistical Package for Social Science software version 27. Bivariate and multivariable regression analyses were carried out to examine the associations between dependent and independent variables. A P-value of <0.05 was considered statistically significant.ResultsThe overall prevalence of recent HIV infection was 9.1% (95% CI: 7.0%, 11.8%). The highest proportion of recent HIV infections was in the year 2019 [9(22.5%)]. The study also found that no formal education (AOR = 18.424, 95% CI = 1.468–231.2), primary educational level (AOR = 22.1, 95% CI = 1.91–256.1, P = 0.013), no formal education (AOR = 18.424, 95% CI = 1.468–231.2, P = 0.028), having sex in the last 12 months (AOR = 5.508, 95% CI = 2.167–15.7, P = <.001), having sex with known/suspected HIV positive (AOR = 4.35, 95% CI = 1.455–13.04, P = 0.009) and Illicit drug use (AOR = 57.8, 95% CI = 16.19–207.5, P = <.001) had higher likelihood of having recent HIV infection.ConclusionThis study found a 9.1% proportion of recent HIV infections, indicating significant ongoing HIV transmission within the community. The study also revealed multiple risk factors for recent HIV infection, including lower educational levels, recent sexual activity, sex with high-risk partners, and drug use. This study emphasizes the significance of improving targeted HIV preventive programs.